Occupation Stress And Its Relation To The Lack Of Mental Energy - Ghidi Abdelkader .; Madjadi Rabeh . (sports creativity, 2025)
Is there a relationship between the work itself and the psychological energy depletion of professors of physical education and sports? and Is there a relationship between the administrative role and the depletion of mental energy among teachers of physical education and sports? and Is there a relationship between the interpersonal relations and the psychological energy depletion of the teachers of physical education and sports